2021
DOI: 10.1002/mop.33037
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing microwave heating uniformity using reconfigurable diffractive beamforming surface

Abstract: Conventional microwave oven suffers nonuniform electric field distribution due to standing wave inside the cavity, requiring improved heating uniformity. Multimode ovens, which are regarded as the most popular method, suffer from relatively limited accuracy and dependency on experimental validations. In this paper, a new class of microwave heating methodology is proposed to achieve heating uniformity improvements through the suppression of undesired standing waves. Microwave absorbers and focusing of electroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…When the additional components being analyzed are not common, low-cost materials are more difficult to implement in industrial applications. Different from methods of adding additional components, Kim 9 suppressed unwanted standing waves and verified the distribution of the electric field in experiments. Jung 10 relocated the wavefront and node positions of the microwave field, controlled selective microwave heating, and heated the required part or objected to the desired temperature.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…When the additional components being analyzed are not common, low-cost materials are more difficult to implement in industrial applications. Different from methods of adding additional components, Kim 9 suppressed unwanted standing waves and verified the distribution of the electric field in experiments. Jung 10 relocated the wavefront and node positions of the microwave field, controlled selective microwave heating, and heated the required part or objected to the desired temperature.…”
Section: Introductionmentioning
confidence: 88%
“…In this article, three frequency shifting algorithms were experimentally compared, and it was demonstrated that the dynamic complementary frequency shifting strategy has wider applicability and better performance. The References 9–11 analyzed and discussed all waveguide characteristics of microwave equipment itself; and examined temperature uniformity by changing the original conditions. However, none of these studies showed temperature fields and electromagnetic fields during the research process.…”
Section: Introductionmentioning
confidence: 99%